The Contestation between Conservative Islamic and Liberal Islamic about Women's Leadership in Indonesia - Rifan Madani; A. Alfira Yuningsih M; Hasse Jubba; Ahamed Sarjoon Razick (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to describe the contestation of conservative Islam and liberal Islam in its views on women's leadership in Indonesia. The data in this study were taken from documents through a review of literature studies with a phenomenological approach. The document is in the form of books, journals, and data on women's leadership. Data is processed through three stages; reviewing the content of the document, describing systematically and objectively, narrating the comparisons found. This study found that there are three aspects that are different views between conservative Islam and liberal Islam regarding women's leadership in Indonesia, namely aspects of legality, capacity, and nature of association. There is no absolute justification for the two groups, as both have strong arguments about their respective views on women's leadership in Islam.